The Role and Mechanism of Lysine Methyltransferase and Arginine Methyltransferase in Kidney Diseases - Zhou, Xun; Chen, Hui; Li, Jinqing; Shi, Yingfeng; Zhuang, Shougang; Liu, Na (Frontiers in Pharmacology, 2022)
Methylation can occur in both histones and non-histones. Key lysine and arginine methyltransferases under investigation for renal disease treatment include enhancer of zeste homolog 2 (EZH2), G9a, disruptor of telomeric silencing 1-like protein (DOT1L), and protein arginine methyltransferases (PRMT) 1 and 5. Recent studies have shown that methyltransferases expression and activity are also increased in several animal models of kidney injury, such as acute kidney injury(AKI), obstructive nephropathy, diabetic nephropathy and lupus nephritis. The inhibition of most methyltransferases can attenuate kidney injury, while the role of methyltransferase in different animal models remains controversial. In this article, we summarize the role and mechanism of lysine methyltransferase and arginine methyltransferase in various kidney diseases and highlight methyltransferase as a potential therapeutic target for kidney diseases.